Cytotoxicity evaluation of two root canal sealers and a commercial calcium hydroxide paste on THP1 cell line by Trypan Blue assay (Journal of Applied Oral Science, 2009)
OBJECTIVE: The aim of this investigation was to evaluate the cytotoxicity of two brands of root canal sealers, epoxy-resin based and zinc oxide-eugenol based, and one commercial calcium hydroxide paste on a monocyte cell line THP-1. MATERIAL AND METHODS: Undiluted (crude extract) and diluted extracts to 10%, 1%, 0.1%, 0.01%, 0.001% and 0.0001% of the sealers were tested for cytotoxicity to THP-1 cells using the trypan blue assay. Extracts were obtained according to ISO standard. Data were analyzed statistically by the Kruskal-Wallis and Mann-Whitney tests at 5% significance level. RESULTS: Crude extract of AH Plus and Fill Canal killed approximately 90% of THP-1 cells versus 36% of THP-1 cells killed by L&C crude extract (p